Clinical parameters of ovarian hyperstimulation syndrome following different hormonal triggers of oocyte maturation in IVF treatment. (6th March 2018) - Abbara, A.; Islam, R.; Clarke, S.A.; Jeffers, L.; Christopoulos, G.; Comninos, A.N.; Salim, R.; Lavery, S.A.; Vuong, T.N.L.; Humaidan, P.; Kelsey, T.W.; Trew, G.H.; et al.
Summary: Objective: Ovarian hyperstimulation syndrome (OHSS) is a serious iatrogenic condition, predominantly related to the hormone used to induce oocyte maturation during IVF treatment. Kisspeptin is a hypothalamic neuropeptide that has recently been demonstrated to safely trigger final oocyte maturation during IVF treatment even in women at high risk of OHSS. However, to date, the safety of kisspeptin has not been compared to current hormonal triggers of oocyte maturation. Design: We conducted a retrospective single‐centre cohort study investigating symptoms and clinical parameters of early OHSS in women at high risk of OHSS (antral follicle count or total number of follicles on day of trigger ≥23) triggered with human chorionic gonadotrophin (hCG) (n = 40), GnRH agonist (GnRHa; n = 99) or kisspeptin (n = 122) at Hammersmith Hospital IVF unit, London, UK (2013‐2016). Results: Clinical Parameters of OHSS : Median ovarian volume was larger following hCG (138 ml) than GnRHa (73 ml; P  < .0001), and in turn kisspeptin (44 ml; P  < .0001). Median ovarian volume remained enlarged 20‐fold following hCG, 8‐fold following GnRHa and 5‐fold following kisspeptin compared to prestimulation ovarian volumes. Mean (±SD) ascitic volumes were lesser following GnRHa (9 ± 44 ml) and kisspeptin (5 ± 8 ml) than hCG (62 ± 84 ml; P  < .0001). Symptoms of OHSS were most frequent following hCG and least frequent following kisspeptin. Diagnosis of OHSS: The odds ratio for OHSS diagnosis was 33.6 (CI 12.6‐89.5) following hCG and 3.6 (CI 1.8‐7.1) following GnRHa, when compared to kisspeptin. Conclusion: Triggering oocyte maturation by inducing endogenous gonadotrophin release is preferable to the use of exogenous hCG in women at high risk of OHSS.